Hernias diafragmáticas congénitas. - Hernández Amador, Guillermo; Morandeira Martín, Ángel; Osorio Acosta, Vicente; Yelín Gringos, Samuel; Cabrera Pérez, Armanda (Revista Cubana de Pediatría, 2023)
Anatomía, embriología, signos y síntomas, diagnóstico diferencial, tratamiento.